2020
DOI: 10.1016/j.psychres.2020.112992
|View full text |Cite
|
Sign up to set email alerts
|

Psychological symptoms of ordinary Chinese citizens based on SCL-90 during the level I emergency response to COVID-19

Abstract: A B S T R A C TThe World Health Organization (WHO) has declared that the Corona Virus (COVID-19) has become a global pandemic. This study aimed to investigate the psychological symptoms of ordinary Chinese citizens during the Level I Emergency Response throughout China. From January 31 to February 2 2020, an online questionnaire, Symptom Checklist 90 (SCL-90) was designed, and differences in GSI T-scores among subgroups were examined by ANOVA. Based on a cut-off point of the GSI T-scores of 63, the overall sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
356
12
41

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(430 citation statements)
references
References 34 publications
21
356
12
41
Order By: Relevance
“…To date, studies from China have produced mixed findings concerning the mental health of different age groups during the COVID-19 crisis. 14,35,36 It is not immediately obvious as to why the mental health of the elderly population is significantly better than that of younger individuals. Similar to elsewhere in the world, they are by far the highest-risk group for death and complications by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies from China have produced mixed findings concerning the mental health of different age groups during the COVID-19 crisis. 14,35,36 It is not immediately obvious as to why the mental health of the elderly population is significantly better than that of younger individuals. Similar to elsewhere in the world, they are by far the highest-risk group for death and complications by COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…However, younger people and those in a medical team, were in the highest risk group, in terms of the severity of psychological symptoms. 44 Another study indicated that individuals over the age of 60 had higher anxiety scores than the general population.12 Losada-Baltar et al (2020),53 however, suggested that it is not chronological age itself, but the negative self-perception of ageing that is related to loneliness and psychological suffering in people during a forced stay at home during the COVID-19 crisis. Elderly people with a positive self-perception of ageing seem to be more resistant to loneliness and distress during the COVID-19 outbreak.…”
Section: Speci C Populationsmentioning
confidence: 99%
“…World Health Organization announced the coronavirus illness 2019 (COVID-19) epidemic, resulted in severe Acute Respiratory Syndrome (SARS) in 2003, designated an epidemic from March 12, 2020 [1,2].…”
Section: Introductionmentioning
confidence: 99%